Microsecond molecular dynamics simulations of Mg²⁺- and K⁺-bound E1 intermediate states of the calcium pump. - L Michel Espinoza-Fonseca; Joseph M Autry; David D Thomas (PLoS ONE)
We have performed microsecond molecular dynamics (MD) simulations to characterize the structural dynamics of cation-bound E1 intermediate states of the calcium pump (sarcoendoplasmic reticulum Ca²⁺-ATPase, SERCA) in atomic detail, including a lipid bilayer with aqueous solution on both sides. X-ray crystallography with 40 mM Mg²⁺ in the absence of Ca²⁺ has shown that SERCA adopts an E1 structure with transmembrane Ca²⁺-binding sites I and II exposed to the cytosol, stabilized by a single Mg²⁺ bound to a hybrid binding site I'. This Mg²⁺-bound E1 intermediate state, designated E1•Mg²⁺, is proposed to constitute a functional SERCA intermediate that catalyzes the transition from E2 to E1•2Ca²⁺ by facilitating H⁺/Ca²⁺ exchange. To test this hypothesis, we performed two independent MD simulations based on the E1•Mg²⁺ crystal structure, starting in the presence or absence of initially-bound Mg²⁺. Both simulations were performed for 1 µs in a solution containing 100 mM K⁺ and 5 mM Mg²⁺ in the absence of Ca²⁺, mimicking muscle cytosol during relaxation. In the presence of initially-bound Mg²⁺, SERCA site I' maintained Mg²⁺ binding during the entire MD trajectory, and the cytosolic headpiece maintained a semi-open structure. In the absence of initially-bound Mg²⁺, two K⁺ ions rapidly bound to sites I and I' and stayed loosely bound during most of the simulation, while the cytosolic headpiece shifted gradually to a more open structure. Thus MD simulations predict that both E1•Mg²⁺ and E•2K+ intermediate states of SERCA are populated in solution in the absence of Ca²⁺, with the more open 2K+-bound state being more abundant at physiological ion concentrations. We propose that the E1•2K⁺ state acts as a functional intermediate that facilitates the E2 to E1•2Ca²⁺ transition through two mechanisms: by pre-organizing transport sites for Ca²⁺ binding, and by partially opening the cytosolic headpiece prior to Ca²⁺ activation of nucleotide binding.